Implementasi Manajemen Tenaga Pendidik dalam Meningkatkan Mutu Lembaga di SMK Al-Khoeriyah Cibeureum Kota Tasikmalaya - Khotimah, Ade Nurul; Komalasari, Imas; Resnasari, Upi Luthfiah (An-Nahdliyyah: Jurnal Studi Keislaman, 2024)
Professional educators contribute to creating quality institutions. To produce professional educators, effective and efficient management is needed. The purpose of this research is to determine the management of teaching staff, the quality of institutions, and the relationship between management of teaching staff in improving the quality of institutions at Al-Khoeriyah Cibeureum Vocational School, Tasikmalaya City. Management of teaching staff is reviewed based on planning, procurement, development guidance, transfer promotion, dismissal, compensation and awards. Meanwhile, the quality of the institution is reviewed based on input, process, output and outcome aspects. The approach used is a descriptive qualitative approach. Data collection techniques use interviews, observation and documentation. The results of this research are: 1) management of teaching staff at Al-Khoeriyah Vocational School consists of: a. Planning, formulating positions and then carrying out the recruitment process. b. Procurement, through a selection and placement process according to qualifications. c. Development coaching is carried out to improve the professionalism of educators. d. Promotion of transfers, providing updates in duties and positions. e. Dismissal at the request of the elderly. f. Compensation and awards are given according to the educator's performance. 2) the quality of the institution consisting of: a. Input by planning learning programs, student acceptance. b. The process of implementing learning. c. Output, the result of the process. d. Outcome, graduates who work or continue their education. 3) Carrying out management stages for teaching staff has an impact on improving school quality which is visible in school outcomes.